Práticas corporais educativas: movimento interno e externo do ser interdisciplinar - Almeida, Telma Teixeira de Oliveira (2013)
This study was started with the introduction of a subject called 'Interdisciplinarity, Self knowledge and Educational Practices' as a proposal to add classroom experiences to movements of corporal practices, enabling the construction of the interdisciplinary being. The research took place in the curriculum of the Pedagogy Course in a University in São Paulo City, Brazil. The methodologic field involves collection of written material on the bibliography on everyday research and intervention research.The written documents show the universe of the students who experienced the proposed educational practices. During the research in which the researcher gradually built her own interdisciplinary journey, there were different experiences: invaluable personal meetings, book and article readings, imagetic experiences, debates and detailed registers on the encounters and research developed, including the ones in the Group of Studies and Research on Interdisciplinarity - GEPI, at PUCSP. The theoretical references were based in authors like Fazenda, Merleau Ponty, Pineau, Espírito Santo, Nonaka and Takeuchi, Capra, among others considered important for the study. It was detected that the process of knowledge creation feeding innovation can promote meaning and strengthen the perceptions of each one involved in the research. When the subject experiences a variety of situations, makes reflections on them, either internally or externally to the group joined, discussing, narrating the own stories, creating new understanding and perceptions, he / she becomes essential to new activities inside our outside the school environment. Experiencing such stages and processes, inhabited by Interdisciplinarity and wholeness of the human being, as innovative possibilities triggering creativity, will bring a contribution to the educators in the field of Teacher Development. Processes of Interdisciplinarity and Selfknowledge can be the bases for more elaborate practices involving the concepts of body and movement, contributing for the (trans)formation process of educators. Educators who are more aware that the doing can on have meaning when centered in the being in movement